The toxicity and sublethal effect of botanical insecticides against the larvae of green lacewings, Chrysoperla nipponensis( neuroptera : chrysopidae) - Md Husin, Siti Khadijah (2017)
Green lacewing, Chrysoperla nipponensis is a common predator of insect pests particularly the leaf sucking insects and is commonly found in vegetable crops. Green lacewing is an important predator of arthropod pests such as aphids, psyllids, thrips and whiteflies. Green lacewing belongs to the family of Chrysopidae. Synthetic insecticides are commonly used to control insect pests and could be harmful to the C. nipponensis. The alternative is to use plant based insecticides. These insecticides are less toxic than synthetic insecticides to the predators and not very harmful to the humans and environments. However, the toxicity of botanical insecticides against C. nipponensis is not well known. A laboratory study was conducted to determine the toxicity and sub lethal effect of four different types of botanical insecticides against larvae of green lacewing. The insecticides were neem, rotenone, garlic oil and entomic. The bioassay was conducted by dipping the leaves into the solution and allowed them to dry at room temperature. The third instar larvae of the green lacewing were exposed to the treated leaf. The mortality of the larvae and sub lethal effect were recorded after 24, 48, 72, 96 and 120 hours. One larva was used per treatment with a minimum of 10 replicates per treatment. Data were subjected to Analysis of Variance (ANOVA) and means separation by Tukey test. The order of the toxicity was rotenone > neem > bralic > entomic. The LC₅₀ of rotenone was 68.19μg/ml while entomic was 949.14μg/ml.